The Effect of Lifestyle, Price Perception, And Location on Purchasing Decisions at Thrift Club Studios Denpasar - Nirmala, Ni Kadek Intan; Agung, Anak Agung Putu; Utami, Ni Made Satya (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
The objective of this study was to examine the correlation between lifestyle, price perception, and location in influencing purchasing decisions. The present study employed quantitative methodologies. The population of this study comprised consumers of Thrift Club Studios Denpasar who had made purchases at the aforementioned establishment. The sample size was determined to be 95 individuals. The data processing in this study was carried out through a series of analytical techniques, including reliability testing, validity testing, classical assumption testing, multiple correlation testing, multiple linear regression analysis, coefficient of determination testing, F-test, and t-test. The findings of the study indicate that lifestyle exerts a substantial positive influence on purchasing decisions, price perception demonstrates a significant positive impact on purchasing decisions, and location exhibits a substantial positive impact on purchasing decisions. It is the author's hope that Thrift Club Studios Denpasar will consistently offer a comprehensive array of products that align with buyers' needs, thereby establishing itself as a leading choice in the market. To this end, the implementation of regular discounts and the augmentation of signage to enhance visibility from major thoroughfares and public spaces are recommended. Furthermore, the pursuit of products that are of superior quality, competitively priced, and highly functional is advised.